PENYULUHAN REGULASI EMOSI: UPAYA PENINGKATAN KETERAMPILAN REGULASI EMOSI PADA SISWA SMK NEGERI 4 SURAKARTA - Satriyadanie, Annisa Siti Solikah; Arianti, Endah Fajri (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Adolescence is a critical developmental stage marked by intense biological, social, and emotional changes. One of the major challenges faced by adolescents is managing their emotions in a healthy way. Poor emotional regulation can lead to negative outcomes such as aggression, anxiety, and delinquent behavior. This community service activity aimed to provide education and training on emotional regulation to students at SMK Negeri 4 Surakarta through theoretical explanations and practical methods, including breathing techniques and the butterfly hug. The program was carried out in three stages: planning, implementation, and evaluation, using interactive presentations and hands-on exercises. The results showed an improvement in students’ understanding of the importance of emotional regulation and their ability to identify, manage, and express emotions adaptively. Post-activity evaluation indicated increased emotional awareness and the application of self-regulation strategies in handling academic and social pressures. This activity demonstrates that emotional regulation training is effective in helping adolescents build positive emotional skills that support psychological well-being and long-term success.